Diagnosis of adult polycystic kidney disease by genetic markers and ultrasonographic imaging in a voluntary family register. Issue 2 (February 1994) - Elles, R G; Hodgkinson, K A; Mallick, N P; O'Donoghue, D J; Read, A P; Rimmer, S; Watters, E A; Harris, R
Abstract : Diagnosis of autosomal dominant adult polycystic kidney disease (APKD) is possible by ultrasonographic scanning (USS) or by using DNA markers linked to the PKD1 locus. Ultrasonography is complicated by the age dependent penetrance of the gene and linkage studies are subject to recombination errors owing to meiotic crossing over and locus heterogeneity. This study draws on data collected from a voluntary family register of APKD over 10 years. Records of 150 families were examined, ultrasound reports were obtained from 242 people at 50% prior risk, and 37 families were typed for DNA markers. The fraction of APKD resulting from loci unlinked to PKD1 (designated PKD2 here) was calculated at 2.94% (upper confidence limit 8.62%). Some subjects who were negative on initial scan later gave a positive scan, but there was no example of a definite gene carrier aged over 30 giving a negative scan. In families large enough for linkage analysis, most people who were at 50% prior risk could be given a final risk below 5% or above 95%, by using combined ultrasound and DNA studies.